Sustainable composites for aerospace applications - Jawaid, Mohammad; Thariq, Mohamed (Woodhead Publishing, 2018)
Annotation This title presents innovative advances in the fabrication, characterisation and applications of LDH polymer nanocomposites. It covers fundamental structural and chemical knowledge and explores various properties and characterisation techniques, including microscopic, spectroscopic and mechanical behaviours. Users will find a strong focus on the potential applications of LDH polymer nanocomposites, such as in energy, electronics, electromagnetic shielding, biomedical, agricultural, food packaging and water purification functions.
Keywords: Airplanes -- Materials.; Space vehicles -- Materials.; Composite materials.; Aerospace engineering.; elektronické knihy; electronic books